A Comparison of Current Guidelines of Five International Societies on Clostridium difficile Infection Management. Issue 3 (September 2016) - Fehér, Csaba; Mensa, Josep
Abstract Clostridium difficile infection (CDI) is increasingly recognized as an emerging healthcare problem of elevated importance. Prevention and treatment strategies are constantly evolving along with the apperance of new scientific evidence and novel treatment methods, which is well-reflected in the differences among consecutive international guidelines. In this article, we summarize and compare current guidelines of five international medical societies on CDI management, and discuss some of the controversial and currently unresolved aspects which should be addressed by future research.